The Role of the Senses in St. Gregory of Nyssa’s Immaterialist Conception of Man - Kotkowska, Elżbieta (Warszawskie Studia Teologiczne, 2024)
St. Gregory of Nyssa is a representative of philosophical immaterialism with theological justification. He is one of the first philosophers to treat philosophy more creatively than apologetically in the revelatory context. For him, man is a spirit just like God the Creator. However, the soul expresses itself externally and people communicate with each other through the senses. The following key questions then come to the fore: In his immaterialist vision of reality, how does Gregory present and justify the role of the senses in relation to the Greek interpretation of νοῦς? And why is the role of the senses only auxiliary in true knowledge that goes beyond what is visible and tangible?